The girl at the back of the bus - Harrison, Suzette D. (Bookouture, 2021)
A heartbreaking and inspirational novel about redemption, family secrets, and the spirit of survival found at the hardest time. Montgomery, Alabama, 1955. On a cold December evening, Mattie Banks packs a suitcase and leaves her family home. Sixteen years old and pregnant, she has already made the mistake that will ruin her life and disgrace her widowed mother. Boarding the 2857 bus, she sits with her case on her lap, hoping that the driver will take her away from disaster. Instead, Mattie witnesses an act of bravery by a woman named Rosa Parks that changes everything. But as Mattie strives to turn her life around, the dangers that first led her to run are never far away. Forging a new life in a harsh world at constant risk of exposure, Mattie will need to fight to keep her baby safe. Atlanta, Georgia, present day. Ashlee Turner is going home. Her relationship in ruins, her career held back by prejudice, she is returning to the family who have always been her rock. But Ashlee's home is not the safe haven she remembers. Her beloved grandmother is dying and is determined to share her story before she leaves.... When Ashlee finds a stack of yellowing letters hidden in her nana's closet, she can't help the curiosity that compels her to read, and she uncovers an old secret that could wreak havoc on her already grieving family. As she tries to make sense of what she has learned, Ashlee faces a devastating choice: to protect her loved ones from the revelations or honor her grandmother's wishes and follow the path to the truth, no matter where it may lead.